2008
DOI: 10.1016/j.jasms.2008.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Study on the photocatalytic degradation of methyl orange in water using Ag/ZnO as catalyst by liquid chromatography electrospray ionization ion-trap mass spectrometry

Abstract: A nanocrystal catalyst Ag/ZnO was successfully synthesized using a simple solvothermal method in this study. This catalyst was characterized by X-ray diffraction (XRD) and transmission electron microscopy (TEM). The results showed that this catalyst was composed of metallic Ag and ZnO. The photodegradation of methyl orange (MO) was investigated in aqueous suspension containing Ag/ZnO catalyst under UV irradiation. Liquid chromatography coupled with electrospray ionization ion-trap mass spectrometry was applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(108 citation statements)
references
References 29 publications
7
90
0
Order By: Relevance
“…These charges are usually named as valence band hole and conduction band electrons, which may participate in the formation of active oxidising species such as hydroperoxyl radicals, hydroxyl radicals, hydrogen peroxide and super oxide [1,3,10,40]. Most of the literature attributes the oxidation of stringent organic compounds to mainly the positive hole and/or hydroxyl radical [1,3,14,17,18,39,[41][42][43][44]. These mechanisms are well known and will contribute to the overall oxidation of MB reported here.…”
Section: Proposed Reaction Mechanismmentioning
confidence: 87%
See 1 more Smart Citation
“…These charges are usually named as valence band hole and conduction band electrons, which may participate in the formation of active oxidising species such as hydroperoxyl radicals, hydroxyl radicals, hydrogen peroxide and super oxide [1,3,10,40]. Most of the literature attributes the oxidation of stringent organic compounds to mainly the positive hole and/or hydroxyl radical [1,3,14,17,18,39,[41][42][43][44]. These mechanisms are well known and will contribute to the overall oxidation of MB reported here.…”
Section: Proposed Reaction Mechanismmentioning
confidence: 87%
“…Most studies have focused on the characterisation of the photocatalytic nature of ZnO [9][10][11][12][13][14][15][16]. Fewer studies have focussed on reaction intermediate and product quantification and analysis [1,[17][18][19], with fewer still aiming to determine the impact and relationship of the photocatalyst surface and solution reactions to this reaction intermediate and product spectrum. Furthermore, most researchers have used powder ZnO to evaluate various parameters that may govern photocatalysis.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that most of the MO was degraded in 60 min, although, other MO derivatives are still present in solution as shown by the TOC reduction results. Reference [7] studied the photocatalytic degradation of MO in water using Ag/ZnO as a catalyst. They reported that irradiation of MO after 10 min produces other forms of methyl groups such as monohydroxlated products.…”
Section: ) Effect Of Superficial Gas Velocity On the Bubble Sizementioning
confidence: 99%
“…Methyl orange (MO) is an azo dye that has been widely used in textiles, foodstuffs, paper and the leather industries [7]- [9]. However, the release of MO and its products into the environment causes serious pollution problems [10].…”
Section: Introductionmentioning
confidence: 99%
“…MO degradation reaction is a First Order reaction [14] with MO transfer into transparent intermediate products.…”
Section: Experiments Detailsmentioning
confidence: 99%